(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article examines the methodological aspects of teaching listening and their practical application at the stages of selecting audio materials, preparing exercises and conducting classes. The article specifies the reasons why teaching listening as one of the types of speech activity plays an important role in the process of foreign language education.